1999
DOI: 10.1074/jbc.274.1.170
|View full text |Cite
|
Sign up to set email alerts
|

β-Lactoglobulin Binds Palmitate within Its Central Cavity

Abstract: Bovine ␤-lactoglobulin (␤-Lg) has been studied extensively in both the isolated and the naturally occurring states. It is a commercially important whey protein of obvious nutritional value but, so far, one that has no clearly identified biological function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
304
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 310 publications
(326 citation statements)
references
References 33 publications
(26 reference statements)
18
304
0
Order By: Relevance
“…Shown in Figure 1a is an ESI mass spectrum acquired in positive ion mode for an aqueous solution of Lg (12 μM) and PA (10 μM) at pH 8.5 and 25°C. At this pH and temperature, Lg is present only as monomer in solution [23]. Inspection of the mass spectrum reveals abundant signal corresponding to protonated Lg n+ ions, at n=7 and 8, and protonated 1:1 complex, (Lg + PA) n+ , at the same charge states.…”
Section: Resultsmentioning
confidence: 99%
“…Shown in Figure 1a is an ESI mass spectrum acquired in positive ion mode for an aqueous solution of Lg (12 μM) and PA (10 μM) at pH 8.5 and 25°C. At this pH and temperature, Lg is present only as monomer in solution [23]. Inspection of the mass spectrum reveals abundant signal corresponding to protonated Lg n+ ions, at n=7 and 8, and protonated 1:1 complex, (Lg + PA) n+ , at the same charge states.…”
Section: Resultsmentioning
confidence: 99%
“…Mature bovine b-lactoglobulin has 162 residues, and is a member of the lipocalin protein superfamily~Flower, 1994, 1996!. Members of this family have a distinctive eight-stranded b-barrel structure, the central cavity of which binds a variety of hydrophobic molecules~Banaszak et al, 1994!. In the case of BLG, the primary site for fatty-acid binding has recently been established crystallographically to be inside this cavity~Qin et al, 1998b;Wu et al, 1999!. The structure of BLG is now reliably known following two independent redeterminations of the structure in the triclinic~lattice X!~Brownlow et al, 1997!…”
mentioning
confidence: 99%
“…Several studies have clearly demonstrated that the binding stoichiometry between retinol or palmitic acid and LG is 1 where the central calyx of LG is responsible for retinol and palmitic acid binding, [21][22][23] but whether the binding of vitamin D to LG is 1 or 2 remains uncertain. Wang et al proposed that LG possesses two potential binding sites for vitamin D: one is in the calyx formed by a -barrel and the other is near an external hydrophobic pocket between the R-helix and the -barrel.…”
Section: Resultsmentioning
confidence: 99%
“…It also pointed out site 2 ( Figure 2b) as a possible second binding site for palmitic acid (46%) and vitamin D 3 (20%). However, since the binding stoichiometry between palmitic acid and LG is 1 (Table 1) and the calyx is the only available binding site for palmitic acid; 21 we ruled out site 2 as a particular site for palmitic acid binding. This site is located among the C-terminal loop, -strand C, and -strand D. Since -strand D is thermally unstable, 7 it is not consistent to the proposed secondary vitamin D binding site that is supposed to be thermally stable in nature (Table 1).…”
Section: Docking Analysis Of the Interaction Betweenmentioning
confidence: 99%
See 1 more Smart Citation